Improved Detection of Recurrent Hepatocellular Carcinomas in Arterial Phase With CAIPIRINHA-Dixon-TWIST-Volumetric Interpolated Breath-Hold Examination. Issue 10 (October 2016) - Qu, Jinrong; Han, Shuai; Zhang, Hongkai; Liu, Hui; Wang, Zhaoqi; Kamel, Ihab R.; Berthold, Kiefer; Dominik, Nickel Marcel; Zhang, Shouning; Dong, Yafeng; Jiang, Lina; Liu, Cuicui; et al.
Abstract : Purpose: The aim of this study was to assess the detection rate of recurrent hepatocellular carcinoma (HCC) in arterial phase using multiarterial CAIPIRINHA-Dixon-TWIST-VIBE (MA-CDT-VIBE). Materials and Methods: Fifty-eight patients with possible recurrence of HCC were retrospectively included in this cohort. Patients were scanned with a prototype dynamic contrast-enhanced breath-hold CDT-VIBE sequence, which included 6 arterial subphases with a temporal resolution of 2.64 seconds on a 3 T scanner. Absence and presence of recurrence was documented by consensus of 2 experienced radiologists using magnetic resonance imaging multiphase imaging and follow-up evaluation. The third of 6 arterial subphases was considered the equivalent-to-conventional single arterial phase from the contrast bolus timing perspective. The detection rate of recurrent HCCs in arterial phase by another 2 independent experienced readers was compared for all 6 arterial subphases of MA-CDT-VIBE and the equivalent-to-conventional single arterial phase. Interreader agreement was also calculated. Results: Of the 55 patients reviewed, 46 patients (201 lesions) had recurrent HCC and 9 patients had no recurrence. There was an excellent interreader agreement for both MA-CDT-VIBE (κ = 1.000, P < 0.0001) and the equivalent-to-conventional single arterial phase (κ = 0.850, P < 0.0001). MA-CDT-VIBE showed the detection rate of 100% for all lesions with the diameter of less than 1 cm, 1 to 2 cm, and more than 2 cm. The equivalent-to-conventional single arterial phase resulted in the detection rate of 81.1% and 83.1% for all recurrent HCCs by the 2 readers, respectively, with 78.7% and 83.6% for lesions measuring less than 1 cm, 79.2% and 81.2% for lesions measuring 1 to 2 cm, and 89.7% and 87.2% for lesions measuring more than 2 cm. Conclusions: Compared with the equivalent-to-conventional single arterial phase, MA-CDT-VIBE with 6 arterial subphases demonstrated higher detection rate of recurrent HCCs in arterial phase and provided a wider arterial observation window, especially for recurrent HCCs less than 2 cm in diameter.